Liraglutide protects against glucolipotoxicity‐induced RIN‐m5F β‐cell apoptosis through restoration of PDX1 expression. Issue 1 (24th October 2018) - Kornelius, Edy; Li, Hsin‐Hua; Peng, Chiung‐Huei; Yang, Yi‐Sun; Chen, Wei‐Jen; Chang, Yan‐Zin; Bai, Yi‐Chiao; Liu, Stanley; Huang, Chien‐Ning; Lin, Chih‐Li
Abstract: Prolonged exposure to high levels of glucose and fatty acid (FFA) can induce tissue damage commonly referred to as glucolipotoxicity and is particularly harmful to pancreatic β‐cells. Glucolipotoxicity‐mediated β‐cell failure is a critical causal factor in the late stages of diabetes, which suggests that mechanisms that prevent or reverse β‐cell death may play a critical role in the treatment of the disease. Transcription factor PDX1 was recently reported to play a key role in maintaining β‐cell function and survival, and glucolipotoxicity can activate mammalian sterile 20‐like kinase 1 (Mst1), which, in turn, stimulates PDX1 degradation and causes dysfunction and apoptosis of β‐cells. Interestingly, previous research has demonstrated that increased glucagon‐like peptide‐1 (GLP‐1) signalling effectively protects β cells from glucolipotoxicity‐induced apoptosis. Unfortunately, few studies have examined the related mechanism in detail, especially the role in Mst1 and PDX1 regulation. In the present study, we investigate the toxic effect of high glucose and FFA levels on rat pancreatic RINm5F β‐cells and demonstrate that the GLP‐1 analogue liraglutide restores the expression of PDX1 by inactivating Mst1, thus ameliorating β‐cell impairments. In addition, liraglutide also upregulates mitophagy, which may help restore mitochondrial function and protect β‐cells from oxidative stress damage. Our study suggests that liraglutide may serve as a potential agent for developing new therapies to reduce glucolipotoxicity.